Power Quality Enhancement Strategy In Grid Connected Dual Voltage Source Inverters Supplying Various Loads - Kshatri, Abinash; Dhami, Sandeep; Bhatta, Amrit (OODBODHAN, 2024)
This paper presents power quality improvement technique for grid connected dual inverter systems supplying non-linear and unbalanced loads. Control algorithms based on instantaneous symmetrical component theory (ISCT) are implemented in the dual voltage source inverter(DVSI). The DVSI enhance power quality by injecting real power and compensating for reactive, harmonic, and nonlinear loads. The dq0 transformation technique is utilized for effective voltage analysis at the Point of Common Coupling (PCC). Detailed simulation results validate the control strategy, demonstrating significant reduction in Total Harmonic Distortion (THD) and improved power quality. THD is analyzed for nonlinear and unbalanced load and reduced below 3%. The findings indicate that the DVSI scheme effectively mitigates harmonic problems, ensuring stable and reliable operation of interconnected grids, and complies with IEEE standards for THD and frequency maintenance.